1996
DOI: 10.1105/tpc.8.12.2265
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a cDNA encoding a plasma membrane-associated, uronide binding phosphoprotein with physical properties similar to viral movement proteins.

Abstract: Oligogalacturonides are structural and regulatory homopolymers from the extracellular pectic matrix of plants. In vitro micromolar concentrations of oligogalacturonates and polygalacturonates were shown previously to stimulate the phosphorylation of a small plasma membrane-associated protein in potato. lmmunologically cross-reactive proteins were detected in plasma membrane-enriched fractions from all angiosperm subclasses in the Cronquist system. Polygalacturonate-enhanced phosphorylation of the protein was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 39 publications
(50 reference statements)
3
68
0
Order By: Relevance
“…These include TCs that encode proteins similar to: (a) purine permease, a high-affinity transporter for adenine, cytosine, and purine derivatives (Gillissen et al, 2000); (b) plantacyanin, a plant-specific blue copper protein, apparently involved in the defense response (Nersissian et al, 1998); (c) a homolog of an Arabidopsis embryospecific protein, whose cellular function is yet to be understood; (d) B12D protein, a protein known to be accumulated in plants during embryo development, seed maturation, and leaf senescence (Aalen et al, 1994;Huang et al, 2001); (e) remorin, a membrane phosphoprotein, suggested to be involved in intercellular communications (Reymond et al, 1996); (f) 2-on-2 hemoglobin, the higher plant homolog of the "truncated" hemoglobins found in bacteria, protozoa, and algae, which possess unique biochemical properties that are likely distinct from those of other plant hemoglobins (Watts et al, 2001); and (g) calmodulinlike proteins.…”
Section: Discussionmentioning
confidence: 99%
“…These include TCs that encode proteins similar to: (a) purine permease, a high-affinity transporter for adenine, cytosine, and purine derivatives (Gillissen et al, 2000); (b) plantacyanin, a plant-specific blue copper protein, apparently involved in the defense response (Nersissian et al, 1998); (c) a homolog of an Arabidopsis embryospecific protein, whose cellular function is yet to be understood; (d) B12D protein, a protein known to be accumulated in plants during embryo development, seed maturation, and leaf senescence (Aalen et al, 1994;Huang et al, 2001); (e) remorin, a membrane phosphoprotein, suggested to be involved in intercellular communications (Reymond et al, 1996); (f) 2-on-2 hemoglobin, the higher plant homolog of the "truncated" hemoglobins found in bacteria, protozoa, and algae, which possess unique biochemical properties that are likely distinct from those of other plant hemoglobins (Watts et al, 2001); and (g) calmodulinlike proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Remorin is a small hydrophilic protein tightly associated to the PM. It binds uronides and is thought to be a plasmodesmataassociated protein involved in cell-to-cell signaling or transport (Reymond et al, 1996). Interestingly, the enzyme isocitrate lyase normally located in glyoxysomes was also found as a component of complex I.…”
Section: Possible Pbm Protein Complexesmentioning
confidence: 98%
“…Overexpression of LjSYMREM1, the ortholog of MtSYMREM1 in Lotus japonicus, resulted in increased root nodulation (Lefebvre et al, 2010;Tóth et al, 2012). Although a potential association between remorins and PD permeability has been proposed (Raffaele et al, 2009), the diversity observed across remorins, plus the fact that remorin mutants generated through different approaches fail to show obvious phenotypes (Reymond et al, 1996;Bariola et al, 2004), have made it challenging to characterize the function of remorins in cell-to-cell transport.…”
mentioning
confidence: 99%